Gaguk Fish Nugget Formulation (Arius Thalassinus) With Addition of Moringa Leaf Flour (Moringa Oleifera): Formulasi Nugget Ikan Gaguk (Arius Thalassinus) dengan Penambahan Tepung Daun Kelor (Moringa Oleifera) - Reva Dianti; Betty Yosephin Simanjuntak; Tetes Wahyu W (Universitas Airlangga, 2023)
The aim of this study was to determine the effect of adding moringa leaf powder to crawfish-based nuggets to the organoleptic quality and calcium content. The initial stage was the preparation of the ingredients, which continued with the manufacture of moringa leaf flour and optimation of nuggets, as well as organoleptic testing. The best formulation was followed by an analysis of calcium levels. This study involved 30 students as panelists. The results of the Kruskal-Wallis test indicated that there were differences in color and texture with a p value= 0,018 and p value= 0,044, respectively. Mann-Whitney test obtained a p value of 0,450, which indicate no difference in color between formulations 1 and 2, but it was found that there was a color difference in the formulation with the addition of 5 grams of moringa leaf powder (p= 0,005). There was an effect of the addition of moringa leaf powder between formulations F2 and F3 with p= 0,034 and p= 0,034 on the texture between formulations 1 and 2, but there was no difference in texture between formulations 1 and 3 with a value of p= 0,800. The calcium levels in nuggets with the addition of 10 grams of leaf flour moringa was 289 mg/%. Nuggets with the addition of 10 grams of moringa leaf flour (F2) were the most preferred by the panelists in terms of taste and texture, and the calcium content could meet 30 percent of the Recommended Dietary Allowance (RDA).